Coil Embolization of Arc of Buhler Aneurysm Rupture - Daniel Yuxuan Ong; Uei Pua (Case Reports in Radiology)
The arc of Buhler (AOB) is a rare anatomical variant. Rupture of an AOB aneurysm is exceedingly rare. In this study, we report a case of AOB aneurysm rupture, which was successfully treated by transcatheter coil embolization. A 74-year-old man presented with symptomatic AOB aneurysm rupture. A computed tomography scan and subsequent angiography revealed the aberrant connection between the common hepatic artery and the superior mesenteric artery. A fusiform AOB aneurysm with focus of active bleeding was detected. This was successfully treated through embolization and sacrifice of the AOB. This suggests that conventional embolization with sacrifice of AOB is a feasible and safe approach.